Influência da deformação em propriedades mecânicas, eletrônicas e de adsorção em nanoestruturas - Oliveira, Raphael Benjamim de (2024)
Two-dimensional nanostructures are the subject of growing interest in science due to their exceptional mechanical, electronic, and thermal properties, among others. As theoretical and experimental studies advance, it has become necessary to analyze how these properties can be influenced through the use of deformation. Our main objective was to analyze how deformation, whether uniaxial or biaxial, affects the various properties of nanostructured systems. Materials such as graphene, α-graphene, β-graphene, and γ-graphene, hexagonal boron nitride, as well as heterostructures composed of carbon, boron, and nitrogen. To carry out these investigations, we used computer simulations. We used methodologies with classical approximations, through molecular dynamics, and methodologies with quantum approximations, through Density Functional Theory, to estimate the physical properties of the structures presented.